70 years of the Military Technical Courier - Gaćeša, Nebojša (Vojnotehnički glasnik / Military Technical Courier, 2022)
This Editorial marks the jubilee which the scientific journal Military Technical Courier celebrates in 2022 - 70 years of regular and continuous publication. On this occasion, the Editorial Office expresses gratitude to institutions and individuals who have contributed most to the progress and success of the Journal.